Elevated-CO2 Response of Stomata and Its Dependence on Environmental Factors - Xu, Zhenzhu; Jiang, Yanling; Jia, Bingrui; Zhou, Guangsheng (Frontiers in Plant Science, 2016)
Stomata control the flow of gases between plants and the atmosphere. This review is centered on stomatal responses to elevated CO2 concentration and considers other key environmental factors and underlying mechanisms at multiple levels. First, an outline of general responses in stomatal conductance under elevated CO2 is presented. Second, stomatal density response, its development, and the trade-off with leaf growth under elevated CO2 conditions are depicted. Third, the molecular mechanism regulating guard cell movement at elevated CO2 is suggested. Finally, the interactive effects of elevated CO2 with other factors critical to stomatal behavior are reviewed. It may be useful to better understand how stomata respond to elevated CO2 levels while considering other key environmental factors and mechanisms, including molecular mechanism, biochemical processes, and ecophysiological regulation. This understanding may provide profound new insights into how plants cope with climate change.